The determinant factors in fostering student anti-corruption behavior through citizenship education - Rizal Fahmi; Tubagus Saputra; Imam Solehudin; Intan Indah Megasari; Ari Febrian (Jurnal Civics: Media Kajian Kewarganegaraan, 2021)
Anti-corruption behavior is an excellent thing to get used to students. Efforts in this direction can be made through Citizenship Education. It is found that the determinant factors that determine the success of these efforts, therefore, why and how these factors can be the key to fostering anti-corruption behavior through Citizenship Education. The researcher's approach in this research is qualitative with a case study method to obtain in-depth answers to the problems above. Data collection techniques in this study were interviews, observations, documentation studies, and field notes. The findings of this study are that the approach as a friend and the habit of being honest in learning civics education is a determining factor in efforts to foster anti-corruption behavior in students at SMK Negeri 9 Bandung.